Early Life Glucocorticoid Exposure Modulates Immune Function in Zebrafish (Danio rerio) Larvae - van den Bos, Ruud; Cromwijk, Suzanne; Tschigg, Katharina; Althuizen, Joep; Zethof, Jan; Whelan, Robert; Flik, Gert; Schaaf, Marcel (Frontiers in Immunology, 2020)
In this study we have assessed the effects of increased cortisol levels during early embryonic development on immune function in zebrafish (Danio rerio) larvae. Fertilized eggs were exposed to either a cortisol-containing, a dexamethasone-containing (to stimulate the glucocorticoid receptor selectively) or a control medium for 6 hours post-fertilisation (0-6 hpf). First, we measured baseline expression of a number of immune-related genes (socs3a, mpeg1.1, mpeg1.2 and irg1l) 5 days post-fertilisation (dpf) in larvae of the AB and TL strain to assess the effectiveness of our exposure procedure and potential strain differences. Cortisol and dexamethasone strongly up-regulated baseline expression of these genes independent of strain. The next series of experiments were therefore carried out in larvae of the AB strain only. We measured neutrophil/macrophage recruitment following tail fin amputation (performed at 3 dpf) and phenotypical changes as well as survival following LPS-induced sepsis (150 μg/ml; 4-5 dpf). Dexamethasone, but not cortisol, exposure at 0-6 hpf enhanced neutrophil recruitment 4 hours post tail fin amputation. Cortisol and dexamethasone exposure at 0-6 hpf led to a milder phenotype (e.g. less tail fin damage) and enhanced survival following LPS challenge compared to control exposure. Gene-expression analysis showed accompanying differences in transcript abundance of tlr4bb, cxcr4a, myd88, il1β and il10. These data show that early-life exposure to cortisol, which may be considered to be a model or proxy of maternal stress, induces an adaptive response to immune challenges, which seems mediated via the glucocorticoid receptor.